Tertullian and the Montanism - Stefanov, Archimandrite (Forum Theologicum Sardicense, 2025)
Archimandrite Pavel Stefanov, Tertullian and the Montanism. Montanism is a popular ancient Christian movement. Its most ardent followers were in Phrygia, Asia Minor, but during the first eight centuries it spread all over the Mediterranean world. The first Latin Doctor of the Church, Tertullian, was under serious suspicion for sympathies towards the heresy of Montanism, especially in his later years. Many features in his later works align with the montanist conceptions of free emotional expressions of faith and anticlericalism. However, in the actual sources, there is no convincing evidence that he was a heretic or that there was a schism in Carthage during his life. It is likely that his rigorist community was a very small “church” within the framework of the Catholic Church of Carthage.